Description of risk factors in the formation of hydrocarbons during the traditional fish smoking in Abidjan - Ake-Assi, Y.; Sess, A.; Anon, N.; Oga, S.; Kouamé, P.; Bonfoh, Bassirou; Biego, G.H.M. (2014)
A descriptive study allowed to estimate the risks of formation of PAHs (polycyclic aromatic hydrocarbons) in the traditionally smoked fish consumed in the area of Abidjan, Côte d’Ivoire. The study was carried out from surveys on processing methods of fresh fish into smoked fish in the production areas. It took place from September 2009 to March 2012 on three smoking sites: Port-Bouët in the South of Abidjan, Ile Boulay, Abobo-Doumé and Koweït in the South-West of Abidjan and Abobo-Macaci in the North of Abidjan. The main risk factors which were identified in the formation of PAH, are the stakeholders, the smoking sites, the technologies, the handling and the storing. The black color and bitter taste of the fish were identified as sensory indicators of PAH formation in smoked fish.